2007
DOI: 10.1097/01.sih.0b013e31802ccf6c
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Course on Lifesaving Techniques for Third-Year Medical Students

Abstract: This lifesaving techniques course utilizing simulation technology successfully covered objectives previously taught with animal vivisection, increased students' confidence levels in performing lifesaving procedures and was highly accepted by the medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…There were 21 students in the control group and 29 students in the modified curriculum group who consented to participate 9,54.1] in the modified curriculum (p = .77). There was no significant difference between the two groups for either one of these parameters (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 21 students in the control group and 29 students in the modified curriculum group who consented to participate 9,54.1] in the modified curriculum (p = .77). There was no significant difference between the two groups for either one of these parameters (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…7 Previous work has reported on the use of high-fidelity simulation in teaching critical care or ACLS case-based scenarios. [8][9][10] Studies of deliberate practice have also shown that in settings with medical residents and housestaff, the utilization of simulation is effective in improving cardiac arrest care and competency. 11,12 These studies all suggest favorable outcomes with high-fidelity versus lower fidelity simulation in teaching ACLS.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrate that high-fidelity simulations are an effective educational modality in equipping medical students with increased confidence to assess and manage acutely unwell surgical patients. Although studies have also shown that simulation training for medical students increases confidence in the assessment and management of critically ill patients, 11 septic shock, and severe sepsis; 12 medical emergencies; 10 and performing life-saving procedures, 13 improved confidence may not necessarily translate into better performance. For example, Morgan and Hogg demonstrated that there was no correlation between level of confidence and performance in an anesthetic simulation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies recently have addressed this issue and worldwide steps are being taken to impart training to medical students prior to internship through courses like the Emergency Trauma Training Course (ETTC) [3,4], Trauma training aims at providing the essential information and skills that the doctor may then apply to identify and treat life threatening or potentially life threatening injuries. The ABCDE approach of Advanced Trauma Life Support (ATLS) course clearly emphasizes that injury kills in reproducible time frames.…”
Section: Trauma Trainingmentioning
confidence: 99%